VISWAKARMAS GENERAL FEATURES AND THEIR POSITION IN THE SOCIETY - Gopalan, Manjoor (Journal of Dharma, 2001)
Caste is comparatively a new institution in South India, since early Tamil literature is silent about it. p.T. Sreenivasa Iyangar says, in ’A History of South India’ that at the period Of ’Tolkappiyam’ (c. 500 A.D.) caste system. as such did not exist, though its beginnings may be inferred from the poet’s reference to ’anthanar’ (Brahmins), arachans’ (rulers), ’vanikkar’s’ (merchants) and ’velialars’ (farmers) as high (melor) and others as low (kizhor) people. According to Nanchinarkianar (c. 600 A. D.) the ancient commentator of Tolkappiyam, these distinctions were not rigid, as arachans inter-marned from Vellalars. Professor Elangularn Kunjan Pillay says that literary and epigraphic sources prior to the seventh century are silent on caste, While references to it are frequent in the period between the eighth and eleventh centuries